Natural selection in three-spined stickleback - Evans, Sarah (2018)
The evolution of a monophyletic group of species is known as a radiation, although it is often difficult to determine whether they are adaptive or non-adaptive (Gittenberger, 1991). Large scale radiations are often assumed to be due to adaptive radiation without further study, however there are many environmental or genetic factors which may produce the same effect. In this thesis, three-spined stickleback (Gasterosteus aculeatus) from North Uist, Outer Hebrides, Scotland are used as a model organism to explore the role of predation within a suspected adaptive radiation. Firstly, an exploratory study was carried out to establish the viability of using model replica stickleback in order to infer predation rates of stickleback by trout (Salmo trutta). Relative predation rates could be established using this method, on the condition that it was an enclosed system without a seasonal influx of piscivorous fish. Within the stickleback species, armour characteristics (such as dorsal spines and plates) are under selection within different populations. On North Uist, stickleback armour traits differ widely between each loch, however the exact causes are unknown. Selection on armour traits was investigated within five different populations with differing predation regimes, predatory fish or insects. It was hypothesised that lochs containing piscivorous predators would produce heavily armoured stickleback, compared to less armoured stickleback in insect predated lochs. Stickleback from the same cohort were sampled before and after winter, and morphological traits were analysed against length. There was evidence of selection in three lochs containing insect predators, as several armour traits had significantly reduced relative to stickleback length. However, there was no evidence of selection against armour traits in the lochs containing piscivorous fish as the main predator. The reduction of armour traits such as plates and spines in lochs with trout present suggests that there may be an alternative cause, such as an environmental factor, resulting in adaptive radiations within these lochs. Lastly, nucleotide and amino acid mutations that have occurred within stickleback populations since the end of the last ice age were investigated. Three major lineages are currently present: trans-Atlantic, Black Sea and European. With both the European and Black Sea lineages diverging from the ancestral trans-Atlantic lineage, the European sequences, which includes North Uist populations, appear to be accumulating mutations much more quickly than the Black Sea individuals. The high frequency of amino acid changes within European populations suggests that there is adaptive radiation occurring to produce some minor genetic radiations within Europe. On the other hand, the low number of haplotypes seen within the Black Sea lineage suggests that it may be the result of a non-adaptive radiation.